Genome Analysis of Lactobacillus plantarum LL441 and Genetic Characterisation of the Locus for the Lantibiotic Plantaricin C - Flórez, Ana B.; Mayo, Baltasar (Frontiers in Microbiology, 2018)
Bacteriocins are ribosomally-synthesised peptides produced by bacteria with antimicrobial activity. The bacteriocins produced by lactic acid bacteria (LAB) may inhibit food-borne pathogens and spoilage organisms, and therefore have potential as natural preservatives. Lactobacillus plantarum LL441 produces a lantibiotic bacteriocin known as plantaricin C, a pore-forming antimicrobial peptide containing modified amino acids that inhibits cell wall synthesis by forming a complex with the peptidoglycan precursor lipid II. The present work describes the genome sequencing of L. plantarum LL441 and the characterisation of the plantaricin C locus. The draft genome sequence of L. plantarum LL441 consisted of 170 contigs and had a total 3,124,603 bp; the GC content was 44.52%. The plantaricin C locus was found in an 18 kbp-long contig, and consisted of six genes organised in an operon-like arrangement. This locus included the bacteriocin structural gene (plnC), followed by a gene encoding a LanM-like protein thought to be involved in the maturation of plantaricin C, and four downstream genes encoding ABC-type transporter components, probably belonging to its putative immunity and export machinery. plnC encodes a precursor of the bacteriocin, i.e., a 58-amino acid peptide containing a 31-amino acid double-glycine leader peptide and a 27-amino acid core peptide. In silico analysis and hybridisation experiments placed the plantaricin C locus to be located on pLL441-1, a large plasmid of L. plantarum LL441. Joining up the gaps between the contigs by conventional PCR, sequencing of the amplicons, and sequence assemblage, allowed the complete 55.3 kbp pLL441-1 molecule to be established. A portion of pLL441-1 larger than 34 kbp, which included the plantaricin C region, was identified in a plasmid-derived contig from the L. plantarum Nizo 3893 genome. Further, the plantaricin C coding locus (about 8.7 kbp) was shown to share 91% nucleotide identity with a portion of the plasmids pPECL-6 from Pediococcus claussenii ATCC BAA-344 and pL11995-4 from Lactobacillus paracollinoides TMW 1.1995. Knowledge of the sequence of the plantaricin C coding region will help in studying its molecular components and allow their involvement in bacteriocin synthesis to be investigated, facilitating the use of the bacteriocin or its genetic elements in new biotechnological applications.